Argyria in an Older Man With Rheumatoid Arthritis - Soroush Ershadifar; Aida Nasirishargh; Paul Aronowitz (Annals of Internal Medicine: Clinical Cases)
An 80-year-old man was hospitalized for right lower-extremity cellulitis found to have argyria of nail beds.